Quarter-Life Crisis Levels among Sixth-Semester Students in the Guidance and Counseling Study Program - Silmi Nurul Jauza; Muhammad Arif Budiman Sucipto; Ade Bagus Saputra; Ilyas Mubarok; Mei Yara Aida Nachwa (CV Edujavare Publishing, 2026)
Sixth-semester students face degree-completion demands, career preparation, independence, and adult-role formation, making them vulnerable to a quarter-life crisis. Previous studies have largely examined final-year students or associations with specific psychological variables, leaving limited evidence on crisis levels and dominant aspects among sixth-semester Guidance and Counseling students. This study examined the students’ quarter-life crisis level and most dominant aspect, aiming to describe its categories and identify their primary concern. A descriptive quantitative survey used total sampling of all 16 accessible students, an initial 40-item Likert questionnaire, item-validity testing, Cronbach’s alpha, descriptive statistics, hypothetical-score categorization, and aspect-mean comparisons. Results showed 31 valid and 9 invalid items, reliability of 0.809, and a mean score of 83.81; 81.25% of respondents were moderate, 18.75% were low, none were high, and uncertainty and hopelessness about the future were dominant with a mean of 3.48 or 69.69% of the ideal score. The students therefore experienced a moderate quarter-life crisis centered on an unclear future, indicating that guidance and counseling services should prioritize career planning, self-efficacy, decision-making, and anxiety management.